Characterization of kaempferia species and activityguided selection of Kaempferia parviflora Wall. Ex baker for agronomic improvement - Labrooy, Catherine Dharshini (2018)
Kaempferia is a genus of gingers has promising potential to be discovered for their ornamental and medicinal value. Nuclear ribosomal internal transcribed spacer (ITS) sequences and morphological characteristics were used to characterize six Kaempferia species including Kaempferia parviflora Wall. ex Baker, Kaempferia galanga Linn., Kaempferia elegans Wall. ex Baker, Kaempferia pulchra Ridl., Kaempferia angustifolia Roscoe, Kaempferia marginata Carey ex Roscoe. Sequence data showed nucleotide diversity (0.458), estimated values of transition/transversion bias (0.89) and divergence pattern in the Kaempferia genus was inferred using maximum parsimony analysis. The resulting phylogenetic tree from morphological and molecular data both showed congruence with three distinctive groupings within selected Kaempferia species. ITS 4 and 5 sequences are proposed as DNA barcodes for identification of Kaempferia species. In terms of morphological traits, petiole length, plant habit, rhizome colour and leaf variation can be used for preliminary identification of this genus.